2015
DOI: 10.17957/ijab/14.0004
|View full text |Cite
|
Sign up to set email alerts
|

Plant-parasitic Nematodes Associated with Olive Tree in Southern Morocco

Abstract: Plant-parasitic nematodes affect significantly the production of susceptible plants, including olive trees. In this context, nematode communities were determined in soil samples collected from 23 olive growing sites in the Haouz and Souss regions (southern Morocco). These sites corresponded to various modalities: wild (Olea europaea L. ssp. sylvestris) or cropped olive (Olea. europaea L. ssp. europaea), traditional or high-density cropping, rainfed or irrigated. Even free-living nematodes prevailed in most of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 12 publications
3
2
0
Order By: Relevance
“…These conditions induce favourable environments for PPN multiplication, especially irrigation, which enhances the development of roots [ 14 ]. This was consistent with others observations in southern Morocco [ 59 ]. This could explain the high abundance of colonizer species and, consequently, the high pathogenicity (PPI value) of the communities recorded in these cropping conditions.…”
Section: Discussionsupporting
confidence: 94%
“…These conditions induce favourable environments for PPN multiplication, especially irrigation, which enhances the development of roots [ 14 ]. This was consistent with others observations in southern Morocco [ 59 ]. This could explain the high abundance of colonizer species and, consequently, the high pathogenicity (PPI value) of the communities recorded in these cropping conditions.…”
Section: Discussionsupporting
confidence: 94%
“…Relationships between the distribution of PPN genera and soil physico-chemical factors were highlighted. The most dominant genera in Taliouine and Taznakht regionss were positively correlated with loamy and clay soils, in agreement with previous studies (Salahi et al, 2014;Aït-Hamza et al, 2015;Aït Hamza et al, 2018). High abundances of PPNs were observed in loamy soils whilst clay soils exhibited low PPN abundances.…”
Section: Correspondence Of Plant-parasitic Nematode Communities To Edsupporting
confidence: 91%
“…Similarly, clay, sand, and silt contents were significantly (P < 0.05) associated with the PPN communities in this study and could separately define PPN population structures [74,75]. Previous studies [76][77][78] revealed the same results with loamy and clay soils. The sand content effect on PPN occurrence on organic crops is due, probably, to its irreversible impact on soil temperature and pH as well.…”
Section: Effect Of Soil Characteristics On Ppn Abundance In Moroccan supporting
confidence: 77%